Analytical and structural review of the functioning mechanisms of territorial clusters in the system of public-private interaction - Chupryna, Kh.; Mukhin, A.; Rizun, D.; Mykytchenko , B. (Ways to Improve Construction Efficiency, 2024)
An analytical and structural review of the functioning mechanisms of territorial clusters within the framework of public-private interaction represents a key factor in enhancing the efficiency of regional economic development. Territorial clusters function as complex economic structures where enterprises, government authorities, and research institutions interact within the scope of shared objectives related to the development of infrastructure, innovative technologies, and investment projects. In the context of globalization, digitalization, and dynamic market changes, the effective operation of such clusters requires a thorough understanding of the structural and managerial mechanisms that ensure coordination, synergy, and interaction among all participants. Modern approaches to clusterization, interaction modeling, and resource management within regional systems integrate both public and private interests. The use of digital platforms, information-analytical systems, and transparent management mechanisms ensures the resilience and adaptability of cluster structures. Key factors influencing the effectiveness of interaction include legal regulation, institutional support, financial and investment instruments, the level of innovation activity, and strategic project coordination. The role of the state in stimulating investment activity, establishing a regulatory environment, and supporting the integration of private enterprises into unified cluster structures is decisive. Innovative and technological platforms enable optimization of communication processes, resource allocation, and risk management. Public-private partnership serves as a mechanism for the efficient functioning of clusters, facilitates the involvement of additional financial and intellectual resources, and enhances regional competitiveness. Territorial clusters are complex organizational and economic systems that require clear management methodologies, the integration of modern technologies, and analytical support.